Chemically active plasmas for deterministic assembly of nanocrystalline SiC film - Cheng, Q. J. (2013)
Silicon carbide thin films are self-assembled onto crystalline silicon substrate from a sintered SiC target at low substrate temperature of 400 °C in Ar + H2 discharge using inductively coupled plasma (ICP) assisted RF magnetron sputtering system. Surface morphology and structural properties of SiC films are investigated by SEM, XRD, FTIR and EDX. SEM, XRD and FTIR results show that the SiC film deposited at an ICP power of 800 W is 3C-SiC nanocrystalline film while the film deposited without ICP power exhibits an amorphous structure. At ICP power of 800 W, there exists a large amount of dissociated H in the plasma, leading to the structural relaxation of the amorphous network towards the crystalline state. The EDX result shows that elemental compositions of Si and C atoms in both the films are almost stoichiometric.